Antidiabetic, Antioxidant, and Gut Microbiota-Modulating Effects of Cymbopogon citratus Leaf Extract in Nicotinamide-Streptozotocin Induced Diabetic Rats - Omolola Soji-Omoniwa; Oluwadamilola Elizabeth Britto; Precious Comfort Omogoye; Oluwafemi Obed Oluwadare; Darasimi Deborah Adeosun; Mariam Oyeladun Alimi; Ridwan Tobiloba Bolajoko; Celestina Omowunmi Amupitan; Emmanuel Ayokanmi Olufemi; Esther Afifoluwake Orekunrin (Biology, Medicine, & Natural Product Chemistry, 2025)
Cymbopogon citratus Leaf Extract (CCE) is used traditionally to manage diabetes mellitus. The study aimed to to evaluate the effects of its oral administration on gut bacteria composition and antidiabetic effect in nicotinamide and streptozotocin-induced diabetic rats. Thirty-five male Wistar rats were divided into five groups comprising 7 rats each. They were; non-diabetic rats given distilled water (PC), untreated diabetic rats (NC), diabetic rats treated with 2.5 mg/kg glibenclamide (RDC), diabetic rats treated with 200 mg/kg extract (CCE1) and diabetic rats treated with 400 mg/kg extract (CCE2). Fasting blood glucose (FBG), insulin, glycogen, lipid profile, catalase, superoxide dismutase (SOD), reduced glutathione (GSH), malondialdehyde (MDA), serum electrolytes, urea, uric acid, creatinine, bilirubin, albumin, alanine and aspartate amino transferases (ALT, AST), alkaline phosphatase (ALP), gut bacterial count were analysed and bacteria identified. Secondary metabolites in extract were also quantified. Results showed significant reductions (p<0.05) in FBG, low density lipoprotein, triglycerides, cholesterol, urea, sodium, catalase, SOD, GSH, and MDA levels in the CCE1 and CCE2 groups compared to the NC. Glycogen, ALT, AST, ALP, and HDL increased significantly. CCE1 outperformed CCE2 in most biochemical parameters. The total bacterial count increased significantly in the treatment groups and the identified species were L. plantarum, L. lactis, C. leptum and, L. mesenteroides. Key secondary metabolites in CCE were catechin, dihydrocytisine, steroid, aphyllidine, Narigenin, proanthocyanidine, oxalate and phytate. In conclusion, CCE exhibited glucose-lowering, antihyperlipidemic, and antioxidant effects, reversed dysfunction in organ function markers and promoted occurrence of beneficial bacterial. Further research into its nutraceutical potential is recommended.